First common volume ground‐based and space measurements of the mesospheric front in noctilucent clouds. Issue 24 (16th December 2013) - Dalin, P.; Connors, M.; Schofield, I.; Dubietis, A.; Pertsev, N.; Perminov, V.; Zalcik, M.; Zadorozhny, A.; McEwan, T.; McEachran, I.; Grønne, J.; Hansen, O.; et al.
Abstract [1] We report on the first common volume ground‐based and space measurements of the mesospheric front in noctilucent clouds (NLCs). The detailed ground‐based observations were performed with automated digital cameras located at the Athabasca University Geophysical Observatory (Canada) on the night of 29–30 June 2012, while simultaneous space measurements were conducted onboard the Thermosphere Ionosphere Mesosphere Energetics and Dynamics satellite using the Sounding of the Atmosphere using Broadband Emission Radiometry instrument. The large temperature difference of 20–25 K between two different air masses at about 85 km altitude was responsible for the front jump separating the area filled with NLCs from the area with no NLCs. The front jump (soliton) had a pronounced elevation of 12 km up to the altitude of 96 km relative to the undisturbed NLC layer located between 84.5 and 86.3 km. Considering present and previous ground‐based measurements of the NLC height, we conclude that altitude of 96–97 km is the upper limit of possible heights of NLCs.